Intrafraction displacement of prone versus supine prostate positioning monitored by real‐time electromagnetic tracking. (4th March 2013) - Butler, Wayne M.; Merrick, Gregory S.; Reed, Joshua L.; Murray, Brian C.; Kurko, Brian S.
Abstract : Implanted radiofrequency transponders were used for real‐time monitoring of the intrafraction prostate displacement between patients in the prone position and the same patients in the supine position. Thirteen patients had three transponders implanted transperineally and were treated prone with a custom‐fitted thermoplastic immobilization device. After collecting data from the last fraction, patients were realigned in the supine position and the displacements of the transponders were monitored for 5–7 minutes. Fourier transforms were applied to the data from each patient to determine periodicity and its amplitude. To remove auto correlation from the stream of displacement data, the distribution of short‐term and long‐term velocity components were calculated from Poincaré plots of paired sequential vector displacements. The mean absolute displacement was significantly greater prone than supine in the superior–inferior (SI) plane ( 1.2 ± 0.6 mm vs. 0.6 ± 0.4 mm, p = 0.015 ), but not for the lateral or anterior–posterior (AP) planes. Displacements were least in the lateral direction. Fourier analyses showed the amplitude of respiratory oscillations was much greater for the SI and AP planes in the prone versus the supine position. Analysis of Poincaré plots confirmed greater short‐term variance in the prone position, but no difference in the long‐term variance. The centroid of the implanted transponders was offset from the treatment isocenter by >   5   mm for 1.9% of the time versus 0.8% of the time for supine. These results confirmed significantly greater net intrafraction prostate displacement of patients in the prone position than in the supine position, but most of the difference was due to respiration‐induced motion that was most pronounced in the SI and AP directions. Because the respiratory motion remained within the action threshold and also within our 5 mm treatment planning margins, there is no compelling reason to choose one treatment position over the other. PACS number: 87.50.st